Performance Improvement in Combating Poverty - Ameebu, Bernadikta Darmawati; Chandrarin, Grahita; Safriliana, Retna (Proceedings of International Conference of Graduate School on Sustainability, 2023)
This research was conducted on property and real estate companies in Indonesia. The data was obtained by accessing the website of the Indonesia Stock Exchange (IDX). The sample in this study was selected using the Purposive Sampling method so that there are 40 property and real estate companies in Indonesia and property, real estate companies registered in Indonesia, stock prices and real estate companies in Indonesia did not do delisting during the pandemic which couldÂ used in this study.Â In this study using panel data. The analytical technique used in this research is multiple regression analysis. The results of this study partially show that Price to Book Value (PBV), Debt to Asset Ratio, and Return on Investment have a significant positive effect on stock returns. Price to Book Value (PBV), Debt to Asset Ratio and Return on Investment have a significant positive effect on stock returns.